Asymptomatic Pelvic Metastasis from Thymic Carcinoma: A Case Report - Surmei-Pintilie, Ecaterina; Narducci, Fabrice; Farre, Isabelle; Kolesnikov-Gauthier, Helene; Boulanger, Thomas; Petit, Stephanie; Porte, Henri; Dansin, Eric (Case reports in oncology, 2014)
Thymic epithelial tumors are rare and often occur somewhere local. Metastatic sites of thymic carcinomas (Masaoka-Koga stage IVb) are mostly seen in the lung, liver and brain. We report a 64-year-old female with an initial diagnosis of thymoma B3 who first showed thoracic recurrences and then an asymptomatic isolated pelvic metastasis from her thymic carcinoma.